PENGARUH PEMBERIAN SMOOTHIES PISANG DAN MELON TERHADAP TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI DI PUSKESMAS SUKARAMI KOTA PALEMBANG - Sintia Ayu Lestari; Afriyana Siregar; Imelda Telisa; Yuli Hartati (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2021)
Background : Hypertension is one of the leading causes of death in the world. World Health Organiation 2019 predicts the prevalence of hypertension in the world by 22% and the Southeast Asian region is ranked third with a prevelence of 25% of the total population, the results of Basic Health Research (Riskesdas) in 2018 showed that, the prevalence of hypertension in Indonesia is 34.11% and the prevalence of hypertension in South Sumatra is 30.44%. The Purpose : The purspose of the study was to find a effect of giving banana and melon smoothies to blood pressure in elderly people with hypertension in the sukarami health center in Palembang. Methods : With this type of research is pseudo experimentation (Quasi Experimentation). With pretest research design – Treatment – Postest with group control. The number of samples in this study was 60 people with 30 as a treatment group and 30 people in the comparison group. Results : The results of this study showed based on the age of most hypertensive patients in palembangsukarami health center aged 55-64 years. Based on gender as a large part is female. Energy Intake, Protein, Fat, Carbohydrates in the good category while for the intake of potassium and vitamin C in the category of less, sodium intake is mostly low salt diet 3. The results of statistical tests show (p<0.05) that there is an influence of banana and melon smoothies on blood pressure in elderly people with hypertension in Palembang Sukarami health center. Conclusion : Consumption of banana smoothies and melons regularly affects the decrease in blood pressure of hypertensive patients